Repellent effect of Essential oil from Ocimum basilicum against Rhyzopertha dominica (Coleoptera: Bostrichidae) and Tribolium castaneum (Coleoptera: Tenebrionidae) - Kumar , Ranjeet (Journal of Postharvest Technology, 2016)
The laboratory experiment was conducted to find out the repellent effect of Ocimum basilicum against Rhyzopertha dominica and Tribolium castaneum by paper disk method. Among the tested concentrations maximum repellency 98.20 percent was observed in 3 percent concentration of Ocimum basilicum followed by 90.06 and 88.38 percent at 2 and 1 percent concentration respectively against Rhyzopertha dominica. The maximum repellency percentage 99.56 recorded at 3 percent concentration of Ocimum basilicum followed by 98.69 and 95.96 percent at 2 and 1 percent concentration respectively. The tested essential oil from Ocimum basilicum showed strong repellent effect against both stored grain insects.